Indole alkaloids from the roots of Nauclea officinalis and their chemotaxonomic significance - Shan-Ze Yin; Bao-Chan Liu; Guo-Lan Ma; Jiu-Wei Ma; Xi-Yang Lei; Bin-Bao Wang; Rui Li; Shao-Jie Lu; Wei-Min Gao; Pei-Gang Ouyang; Cai-Feng Ding (Biochemical Systematics and Ecology, 2026)

Next-generation meat frying technologies: Industry 5.0-enabled strategies for ultra-low flavor loss and lipid oxidation - Zhe Wang; Min Zhang; Bhesh Bhandari; Luming Rui (Food Research International, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

Decoupling between chain extension and entanglement via branched structures for ultralow-power biaxially stretched polypropylene capacitor films - Qi Wu; Can Zhao; Enhui Liu; Xuan Wang; Jing Zhou; Rui Han; Min Nie (Chemical Engineering Journal, 2026)

Effect of double-cropping pattern on biological yield and quality of silage corn across different cropping systems in the Hebei region - Liang Song; Min Jia; Quanguo Zhang; Jianghao Wang; Liwei Wang; Rui Guo; Yuanyuan Yan; Jianfeng Wei; Xinghua Li; Wei Song (Next Research, 2026)

From thawing to quality restoration: Advanced thawing technologies for frozen starchy foods toward industry 5.0 - Chao Wang; Min Zhang; Luming Rui (Food Research International, 2026)

Chlorophyll fluorescence imaging for early visual detection and measurement of postharvest discoloration: Potato greening and broccoli yellowing - Dayuan Wang; Min Zhang; Qibing Zhu; Bhesh Bhandari; Luming Rui (Food Research International, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Triply activated localized DNA circuit based on dual enzyme-guaranteed and analyte-stimulated strategy for robust tumor-cell-specific microRNA imaging - Yuanyuan Peng; Xiaoyu Wang; Wanling Cui; Rui Wang; Haiyan Zhao; Ning Zhang; Min Liu; Yushu Wu (Analytica Chimica Acta, 2026)

Acid/alkali pretreatment enhances micro-nano bubble flotation separation of lepidolite and albite - Lianjun Wu; Rui Liao; Min Gan; Baojun Yang; Dezhi Liu; Jun Wang; Guanzhou Qiu (Minerals Engineering, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

Origin of natural gas in the Permian Wujiaping shale formation, Southeast Sichuan Basin: Constraints from gas composition and isotopic geochemistry - Rui Yang; Jianting Xu; Wei Peng; Pengwei Wang; Haotian Liu; Li Zhang; Min Li (Fuel, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Automatic calibration method for the CycLiq constitutive model with focus on liquefaction behaviour - Bin Hu-Yan; Xiaotong Yang; Jian-Min Zhang; Rui Wang (Soil Dynamics and Earthquake Engineering, 2026)

A study on the hydrodynamic performance and wake modulation effect of a twisted pre-swirl stator in a rim-driven thruster - Yi-Ming Hu; Cong Sun; Min Liu; Chun-Yu Guo; Pei-Rui Tang; Yu Zhao; Chao Wang (Ocean Engineering, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Resistome risks of biological wastewater treatment communities: A global dataset of activated sludge, anaerobic digestion, and anammox - Min Xu; Shengchun Qi; Xiaofan Yu; Shiyi Han; Rui Xiao; Jianhua Guo; Changzhi Wang; Ning Zhu; Huijie Lu (Journal of Hazardous Materials, 2026)

Optimization of magnetic field-assisted freezing via response surface methodology and its impact on blueberry freeze-thaw quality - Bowen Chen; Xinqun Zhou; Jing Sun; Rui Wang; Min Zhang; Ning Ji; Tingchao Liu; Bangdi Liu; Lihua Jiang (International Journal of Refrigeration, 2026)

A PINN-driven stress integration paradigm for high-fidelity soil constitutive model considering cyclic response - Yunyi Li; Jian-Min Zhang; Rui Wang (Computers and Geotechnics, 2026)

Mechanistic study on direct oxidation of xylose to xylonic and xylaric acids in base-free medium - Yinghao Wang; Wei Yu; Zhaozhe Li; Rui Min; Wenmao Zhang; Chunmei Li; Feng Du; Wenjuan Yan; Xin Jin; Chaohe Yang (Chemical Engineering Journal, 2026)

Research progresses on the regulatory roles of microRNAs in radiation-induced pulmonary fibrosis - Min Zhu; Haowei Li; Rui Chen; Jianming Cai; Tao Wang; Changjing Zuo (Journal of Molecular Histology, 2026)

ATP6AP2 ameliorates inflammation and pyroptosis in heart failure by promoting lysosome-dependent STING degradation - Xuan Zhao; Hui Zhang; Xinyue Ding; Huimin Wu; Min Li; Nengpin Yin; Junqing Gao; Youlong Xu; Rui Wang; Zhen Qi; Lina Xing; Zongjun Liu (Apoptosis, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Sedimentary DOM composition governs the environmental mobility of palladium in tropical island estuaries - Zhixin Li; Yuyan Liu; Ling Wang; Hongwei Yi; Rui Xu; Jianan Liu; Haofeng Liu; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

Short-term organic fertilizer substitution: effects on crop yield and soil phosphorus dynamics in a rice-rapeseed rotation system - Hui Wang; Wenlong Cheng; Shang Han; Shan Tang; Fahui Jiang; Rongyan Bu; Min Li; Rui Zhu; Mengmeng Tang; Zhenghua Xu; Ji Wu (Journal of Soils and Sediments, 2026)

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Interface-engineered MXene/OCNT fibers for high-performance wearable supercapacitors - Rui Wang; Xupu Jiang; Ting Ding; Wujun Ma; Chuntao Lan; Min Li (Chemical Engineering Journal, 2026)

Exploring the impact of vertical exchanges on surface ozone based on interpretable deep learning - Yinru Chen; Qin'geng Wang; Min Shao; Rui Liu; Chenwu Zhang (Atmospheric Research, 2026)

Research on Dynamic Control of Flood Control Level for Jinxia Reservoir Group Considering Risks - Min Li; Yue Sun; Rui Feng; Wei Ding; Qianning Wang; Jinnan Zhang; Yong Peng; Feilin Zhu (Water Resources Management, 2026)

Postbiotics Derived from Cetobacterium somerae Increase growth, Gut health, and Disease Resistance in Turbot (Scophthalmus Maximus L.) - Wentao Wang; Mengqi Chen; Shufei Liang; Zeheng Li; Wenkai Shi; Zhihao Wang; Rui Shao; Qinghui Ai; Kangsen Mai; Min Wan (Probiotics and Antimicrobial Proteins, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Beyond human vision: Highlighting and detecting inconspicuous defects in citrus fruits using UV-fluorescence imaging and YOLO11 - Dayuan Wang; Min Zhang; Qibing Zhu; Bhesh Bhandari; Luming Rui (Postharvest Biology and Technology, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Alternate straw mulching improves sorghum productivity and profitability via moderating soil temperature and conserving moisture in a hot, drought-prone region - Yuzhang Chen; Xin Liu; Songguo Wu; Wei Mo; Min Li; Xi Liu; Licheng Wang; Rui Li; Lijuan Gong (Field Crops Research, 2026)

Trajectories of vegetation dynamics and their driving factors across China Ecosystem Research Network: A long-term assessment (2000–2024) - Shuyi Zhang; Ziwen Jin; Mengyao Ci; Ke Zeng; Yue Wang; Hanxin Tang; Rui Zhang; Chaolin Cai; Xianzhong Cao; Min Liu (Journal of Geographical Sciences, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Butyrate-induced trained immunity enhances bacterial killing ability of head kidney macrophages in turbot (Scophthalmus maximus L.) - Shu Zhao; Jinjin Zhang; Wentao Wang; Shufei Liang; Mengqi Chen; Rui Shao; Xinmeng Liao; Qinghui Ai; Kangsen Mai; Min Wan (Fish & Shellfish Immunology, 2026)

Characterizing on-road particle number emissions from container diesel trucks using interpretable machine learning - Rui-min Hao; Hong-di He; Hong-mei Zhao; Wen-jian Jia; Zhong-ren Peng; Hui Wang (Atmospheric Pollution Research, 2026)

Modeling and experimental validation of crack-induced bottom-side erosion effects in buried pipelines - Yan-Ning Wang; Tai-Kai Li; Jing-Rui Peng; Xin-Hao Min; Lin-Shuang Zhao (Tunnelling and Underground Space Technology, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Encoding intrinsic rare-earth dissolution selectivity into deep eutectic solvents via coordination-active functional group design - Zhihan Zhang; Guobiao Li; Zhi Wang; Wanhai Xiao; Yong Lin; Shuping Cheng; Rui Min; Jian Wu; Mingqing Liu; Dong Wang (Journal of Cleaner Production, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Ecosystem-specific composition and drivers of plastisphere resistome in freshwater and marine environments - Jianhong Shi; Chaoli Sun; Yinglong Su; Yifan Wu; Min Zhan; Chengyuan Ji; Rui Wang; Baoyi Lv (Environmental Research, 2026)

A Stress-Partitioning-Framework constitutive model for methane hydrate-bearing sediment incorporating dissociation induced deformation - Jialin Xu; Chengshun Xu; Jian-Min Zhang; Rui Wang (Computers and Geotechnics, 2026)

Strain-dependent immunomodulatory activities of lipoteichoic acids from probiotics: From interspecies to intraspecies variation - Yini Liu; Rui Xiao; Min Guo; Jingyu Lu; Jianxin Zhao; Ruojie Zhang; Hao Zhang; Gang Wang; Zipei Zhang (Food Bioscience, 2026)

Experimental investigation and analysis of monotonic and cyclic behaviour of a natural sand in intact and reconstituted states - Xiaotong Yang; Wenming Peng; Jian-Min Zhang; Jian Li; Qixun Luo; Fulong Ma; Rui Wang (Engineering Geology, 2026)

Bioaccumulation and trophic transfer of phthalate esters in mangrove food web - Jianan Liu; Yuyan Liu; Siwen Chen; Rui Xu; Haofeng Liu; Zefeng Wang; Xianbiao Lin; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Reducing grain arsenic and extracting soil arsenic in paddies by an integrated ridge–furrow and ferrihydrite–PVA membrane system - Jing-Min Yang; Qiao-Rui Ren; Zi-Xin Liu; Xin Wang; Dong-Xing Guan; Ya-Nan Dai; He Pei; Bo Peng; Qin-Bo Qin (Journal of Environmental Sciences, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Transpiration-inspired bionic fabric achieving simultaneous hyperspectral and thermal infrared camouflage via dynamic water management - Chuntao Lan; Shiyu Li; Yiwen Gan; Ningjing Song; Muchen Liang; Rui Wang; Lifen Mao; Wujun Ma; Min Li (Chemical Engineering Journal, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

Spatial aggregation trends of cultivated land quality and landscape patterns: A remote sensing analysis - Mengmeng Tang; Wenlong Cheng; Zhengbao Gao; Fahui Jiang; Shang Han; Danyang Xu; Rongyan Bu; Shan Tang; Rui Zhu; Min Li; Hui Wang; Changai Lu; et al. (Applied Soil Ecology, 2026)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Spatiotemporal evolution of urban–rural ozone disparities and the “pollution transfer” effect in rapidly urbanizing regions - Rui Zhang; Shuyi Zhang; Hanxin Tang; Ke Zeng; Yue Wang; Jiarui Zhang; Mengyao Ci; Ziwen Jin; Min Liu (Urban Climate, 2025)

A CPP-ESO controller for robust multi-USV formation under complex environments and communication constraints - Xiaomin Wang; Min Xue; Jialin chen; Bin Dou; Rui Yang; Zhendong Sun (Ocean Engineering, 2025)

Clonal budding and a sessile stalk in conulariids suggested by a new genus from China - Hui Min; Rui-Wen Zong; Xun-Lian Wang (Palaeoworld, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

Sustainable food frying enhanced by AI: A comprehensive review - Xuan Wang; Min Zhang; Chung Lim Law; Luming Rui (Food Research International, 2025)

The threshold concentration capsaicin enhanced salty taste and reduced sodium: Sensory assessment and analysis of physiological and biochemical characteristics of saliva - Tianlong Han; Qiang Liu; Zixuan Wang; Min Wang; Yuting Hou; Shiyu Wang; Yuxuan Sun; Haixia Liu; Rui Chen; Dengyong Liu (Food Chemistry, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Wheat straw incorporation and nitrogen fertilization increase antibiotic resistance gene abundance and dissemination potential in agricultural soil - Feng-Hua Wang; Rui-Ao Ma; Zi-Teng Liu; Xin-Di Zhao; Ruibo Sun; Wenxu Dong; Yuming Zhang; Min Qiao; Si-Yu Zhang (Soil Ecology Letters, 2025)

Corrigendum to “Studies on the regulation of E3 ubiquitin ligase APC3 and its interacting proteins on the tetraspore formation and release in Gracilariopsis lemaneiformis (Rhodophyta)” [Plant Sci. 356 (July) (2025) 112488] - Qiong Wu; Jingyu Zhang; Min Jiang; Jingru Yin; Lu Wang; Rui Chen; Zhenghong Sui (Plant Science, 2025)

The moderating effect of sour and spicy interactive perception and its variation model: A predictive tool for optimizing flavors - Tianlong Han; Shiyu Wang; Yuxuan Sun; Min Wang; Qiang Liu; Haixia Liu; Rui Chen; Dengyong Liu (Food Research International, 2025)

Sequential targeted nanomedicine MPC treats cerebral ischemia-reperfusion injury via neuronal microenvironment reprogramming - Shuya Wang; Ruishi Li; Xiaojing Shi; Tingli Xiong; Wenxuan Zheng; Weimin Qi; Min Liu; Lin Dai; Qian Lin; Rui Huang; Wei Dai; Min Zhou; et al. (Chemical Engineering Journal, 2025)

Air layer-engineered Cf@void@SiCnf composites for enhanced electromagnetic wave absorption - Wenzhao Geng; Limeng Song; Yilin Liu; Haoyuan Lei; Peng Liang; Linan Wang; Hailong Wang; Yanqiu Zhu; Mi Tian; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2025)

Crystal refinement in biaxially stretched capacitor films for enhanced energy storage - Qi Wu; Zhicheng Li; Gang Chen; Shuai Zhang; Wenyan Wang; Weicai Wan; Rui Han; Min Nie (Chemical Engineering Journal, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

Deciphering the multifaceted effects of artificial sweeteners on body health and metabolic functions: a comprehensive review and future perspectives - Qiang Liu; Min Wang; Yuting Hou; Rui Chen; Haixia Liu; Tianlong Han; Dengyong Liu (Critical Reviews in Food Science and Nutrition, 2025)

Seismic performance assessment for high CFRD on thick layered deposit considering various reinforcement measures - Zhao Wang; Wenming Peng; Jian-Min Zhang; Rui Wang (Soil Dynamics and Earthquake Engineering, 2025)

Impact of calcium alginate gel-urea modified dry water on free radical spectral signatures and suppression mechanisms in methane explosions - Bin Peng; Qiuhong Wang; Jun Deng; Chi-Min Shu; Guoqiang Dong; Qingfeng Wang; Chao Ma; Rui Guo; Jianxiong Liu (Process Safety and Environmental Protection, 2025)

The interactions, impacts, and removal strategies of microplastics (MPs) and antibiotic resistance genes (ARGs) in aquatic environments, particularly in wastewater treatment plants (WWTPs) - Ying Wang; Xin-Rui Zhang; Min-Min Qiang; Zheng Huang; Xin-Tao Liu; Run-Mei Li; Zi-Yue Li; Zai-Yong Zhang; Qian-Qian Zhang (Journal of Environmental Chemical Engineering, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Aramid nanofiber-reinforced MXene fibers for flexible supercapacitors - Yiwen Gan; Ningjing Song; Jiaxin Quan; Ting Ding; Xupu Jiang; Rui Wang; Wujun Ma; Chuntao Lan; Min Li; Meifang Zhu (Chemical Engineering Journal, 2025)

Bioinspired conductive-catalytic network accelerates rate-determining steps at cathode-electrolyte interface for high-loading Li-S batteries - Cai-Yun Zhang; Chen-Yang Wang; En-Zhu Zhao; Guowei Yu; Hui-Ling Deng; Rui Huang; Zhao-Yun Wang; Pu Hu; Min Yan; Zhitian Liu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Nickel complex-bridging to enhance electron transport in covalent organic frameworks for efficient photocatalytic uranium reduction - Xiao-Xing Wang; Rui Zhang; Zhi-Hai Peng; Jing-Wen Gong; En-Min Hu; Cheng-Peng Niu; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Low temperature efficient adsorption of toxic gas phosphine over CuCe co-doped nitrogen-rich biochar in an anaerobic environment - Ruoxu Liu; Min Shao; Junjie Ma; Fang Wang; Rui Cao; Zibin Pan; Ping Ning; Jiayu Feng; Shuo Cui; Lijuan Jia (Chemical Engineering Journal, 2025)

A 3D-printed chitosan-based pH-responsive dual functional scaffold for osteomyelitis: synergistic antibacterial and osteogenic treatment - Mingyue Lin; Yijing Stehle; Li Chen; Mao Yang; Ke Zeng; Chenxin Wang; Rui Zhang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Yubao Li; et al. (Carbohydrate Polymers, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Dynamic and pseudo-static analysis of shield tunnels in liquefiable ground with nearby aboveground structures - Tong Zhu; Meng-Xiong Tang; Junguang Huang; Jian-Min Zhang; Rui Wang (Soil Dynamics and Earthquake Engineering, 2025)

Mechanistic insights into the impact of Lincomycin on microalgal-bacterial granular sludge in domestic wastewater treatment - Guihua Wang; Shujuan Meng; Bin Ji; Rui Wang; Min Liao; Xinyu Chang; Yu Liu; Meng Zhang (Journal of Water Process Engineering, 2025)

Physicochemical characteristics, flavor profile, and microbial community of commercial traditional fermented chili pepper in Guizhou (Zao pepper) - Xijuan Zhang; Pei Gao; Qixing Jiang; Yongjun Wu; Shuhan Yang; Xiaojing Zhang; Rui Cao; Jing Wang; Min Jiang; Shaoquan Liu; Peipei Yu; Fang Yang; et al. (Food Bioscience, 2025)

Fabric quantities governing liquefaction resistance and post-liquefaction shear deformation of granular material - Qizhuo Yang; Jian-Min Zhang; Rui Wang (Computers and Geotechnics, 2025)

Two new diarylheptanoids from Curcuma kwangsiensis rhizomes - Shuo-Guo Li; Le Deng; Qiu-Fang Chen; Rui Yang; Cao-Min Zou; Shu-Mei Wang; Meng-Hua Wu; Jiang Meng (Natural Product Research, 2025)

Insights into ROL-driven and ROS-mediated metalloid oxidation and sequestration in the soil-rice iron barrier system - Jing-Min Yang; Xin Wang; Dong-Xing Guan; Rui Huang; Xiong-Hui Ji; Yun-He Xie; Bo Peng; Qin-Bo Qin (Journal of Hazardous Materials, 2025)

Developing a Cas12a-based detection method on the emetic Bacillus cereus strains in infant formulas - Hao Wang; Rui Yin; Yingying Huang; Yan Li; Min Yue (Food Research International, 2025)

The combined application of cis-cyclo(L-Phe-L-Pro) with antimicrobial proline-based 2,5-diketopiperazines significantly enhances anti-breast cancer activity by selectively targeting cancer stem cells - Rui Liu; Bo Sun; Sa-Ouk Kang; Yeonju Hong; Ji-Yoon Yeo; Jun-Hua Wang; Min-Kyu Kwak (Chemico-Biological Interactions, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Ferritinophagy-derived iron causes protein nitration and mitochondrial dysfunction in acetaminophen-induced liver injury - Shi-Min Liang; Jie Shen; Rui-Ting Ma; Nan-Di Du; Rui Wang; Zuo-Min Wu; Min Shan; Shi-Rong Liang; Wei-Rong Hu; Wei Wang; Wei-Wei Sheng; De-Feng Huang; et al. (Toxicology and Applied Pharmacology, 2025)

Improving agricultural mulching to reduce environmental footprint and enhance economic profit across China - Huihui Wei; Yifan Yang; Li Zhang; Zutao Ouyang; Matthew Tom Harrison; Ke Liu; Guojun Sun; Gary Y. Gan; Feng-Min Li; Li Dong; Rui Wang; Bo Wang; et al. (Resources, Conservation and Recycling, 2025)

Studies on the regulation of E3 ubiquitin ligase APC3 and its interacting proteins on the tetraspore formation and release in Gracilariopsis lemaneiformis (Rhodophyta) - Qiong Wu; Jingyu Zhang; Min Jiang; Jingru Yin; Lu Wang; Rui Chen; Zhenghong Sui (Plant Science, 2025)

Effects and mechanisms of microencapsulation on the regulation in typical activities and flavor stability of Sichuan pepper oleoresin used for food processing and storage - Jiong Zhang; Min Zhang; Bhesh Bhandari; Mingqi Wang; Luming Rui (Food Chemistry, 2025)

A new synergistic preservation method for prepared vegetable mixture: HVEF-photocatalyst film-LED preservation enhancement - Dianyuan Wang; Min Zhang; Luming Rui (Food Bioscience, 2025)

Fire ant-inspired bone repair breakthrough: Self-assembly strategy of microspheres driven by physical hydrogen bonding and hydrophobic interactions - Rui Zhang; Yijing Stehle; Li Chen; Ke Zeng; Mingyue Lin; Chenxin Wang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Mao Yang; Yubao Li; et al. (Chemical Engineering Journal, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

Impact of lithofacies categories on inflection-point behaviors in micro-nano pore-structure evolution: Implications for differential reservoir-forming mechanisms and “sweet-spot intervals” identification for marine gas shales - Wei Yang; Rui Yang; Min Wang; Shujing Bao; Leilei Yang; Haodong Hou; Yan Song; Zhenxue Jiang; Ke Miao; Liang Xu (Marine and Petroleum Geology, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Long non-coding RNA HOXA11-AS inhibits apoptosis, induces proliferation, and promotes autophagy via the miR-214-3p/ATG12 axis in acute T lymphoblastic leukemia - Rui Zhang; YuanYuan Zhang; XiaoFei Li; ShaoHua Wang; Jiao Li; ShuoChun Shao; Bin Liu; WeiWei Guo; Min Shi (Journal of Molecular Histology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Process modeling guided start-up and stable operation of a pilot-scale mainstream partial denitrification-anammox system - Min Xu; Wenbo Chai; Wanlu Zhu; Yuyan Zhang; Rui Xiao; Changzhi Wang; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

A template-free one-step synthesis of trimetallic nano-triangular structures significantly enhances the sensitivity of lateral flow immunoassays for acetamiprid detection - Jiahao Li; Baoshan He; Wenjie Ren; Ying Liang; Jinshui Wang; Rui Guo; Min Wei; Huali Jin (Analytica Chimica Acta, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

From city to countryside: Unraveling the long-term complex effects of urbanization on vegetation growth in China - Shuyi Zhang; Hongkai Zhu; Ke Zeng; Yiwen Zhang; Ziwen Jin; Yue Wang; Rui Zhang; Breuste Jürgen; Min Liu (Journal of Environmental Management, 2025)

Solar interfacial evaporator based on robust aligned channels bacterial cellulose aerogels for wastewater treatment - Jiyan Li; Min Qiao; Shuo Gao; Tao Zhou; Rui Jiao; Fei Wang; Hanxue Sun; An Li (Journal of Environmental Chemical Engineering, 2025)

Botryorhodine J, a new anti-MRSA depsidone isolated from endophytic fungus Alternaria alternata Pas11 - Wen-Yuan Li; Cheng-Cheng Hu; Jin-Hai Liu; Heng-Jie Wang; Ling-Pan Lu; Min Qiao; Ya-Ling Jiang; Rui Wu (Natural Product Research, 2025)

Clean recovery rare earth elements from NdFeB magnets waste by using AlCl3 solution - A closed-loop process - Zhihan Zhang; Guobiao Li; Zhi Wang; Rui Min; Tao Qi; Dong Wang (Journal of Cleaner Production, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Unexplored role of nanoconfinement in regulating contaminant oxidation pathways for water decontamination: Confined energy driving low-carbon route - Min Tang; Wu Liu; Zhiyong Wang; Zhaoduan Hu; Jinquan Wan; Rui Peng (Chemical Engineering Journal, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

CircTBCK protects against osteoarthritis by regulating extracellular matrix and autophagy - Wei Wang; Yuzhe Sun; Peng Tang; Rui Zhang; Yufeng Jiang; Hongwei Min; Chen Gao (Human Cell, 2025)
Osteoarthritis (OA) is a widespread chronic bone and joint disease for which there is currently no effective preventive or therapeutic treatment. Accumulating evidence indicates that circular RNAs (circRNAs), a class of noncoding RNAs, play critical roles in OA. Therefore, in this study, we aimed to reveal an unexplored circTBCK and elucidate its mechanism of action in the pathological process of OA. The different expression of circTBCK was obtained both in vitro and in vivo. In the in vivo model, mice were induced via destabilization of the medial meniscus (DMM) surgery, while in vitro model, mouse cells like primary chondrocytes of newborn mice and ATDC5 cell line were treated with IL-1β treatment (10 ng/mL for 24 h). The level of circTBCK was examined by quantitative real-time polymerase chain reaction (qRT-PCR). After circTBCK was overexpressed or knocked down, IL-1β treatment was performed, and then, chondrocyte viability was detected via a Cell Counting Kit-8 (CCK-8) assay at 0, 24, 48, or 72 h. To assess type II collagen (Collagen II) expression, immunofluorescence (IF) analysis was used. The levels of mRNAs and proteins related to proliferation, the extracellular matrix (ECM) and autophagy were determined by qRT-PCR and Western blotting. Compared with OA treatment, primary chondrocytes with treatment of both circTBCK overexpression and IL-1βincreased the expression of anabolic factors—Collagen II and SRY-box transcription factor 9 (SOX9), proliferation-related molecules—Ki-67 and proliferating cell nuclear antigen (PCNA), and autophagy-related molecules—Microtubule-associated protein 1 light chain 3 (LC3), B-cell lymphoma 1 (Bcl1), and autophagy-related 5 (Atg5) and decreased Sequestosome 1 (SQSTM1 or P62). In contrast, knockdown of circTBCK aggravated the chondrocyte degeneration induced by IL-1β. Overall, our findings suggest that circTBCK, an unexplored circRNA, could regulate autophagy, proliferation, and the extracellular matrix (ECM) to mitigate the development of OA, suggesting a possible target for OA prevention and therapy.

Enhanced selenite removal performance of zero valent iron-biochar composite by in situ formed Fe2SiO4 during ash-rich biomass pyrolysis - Shunfeng Jiang; Rui Zhang; Zhiquan Wang; Min Zhao; Xiangyong Zheng (Process Safety and Environmental Protection, 2025)

Seismic response of reef-seawater system with steep slope under Scholte wave - Yunyi Li; Jian-Min Zhang; Rui Wang (Ocean Engineering, 2025)

Three-dimensional MOFs confined Anderson-type POMs clusters—Templated fabrication of porous Co-NiMo/Cr2O3 catalyst with superior NH3-SCR catalytic activity - Yu Zhang; Rui Wang; Jingcai Chang; Min Yue; Yong Cai (Fuel, 2025)

Revealing the combined effect of hydroxylamine and hydrazine on nitrogen removal performance of completely autotrophic nitrogen removal over nitrite (CANON) process - Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Bioresource Technology, 2025)

Three new isoquinoline alkaloids from the fermentation of Aspergillus sp. 0338 and their anti-MRSA activities - Min Yang; Miao Dong; Qing-Yang Wu; Shui Yao; Gui Pu; Yue-Yu Ma; Rui-Feng Xiong; Qiu-Fen Hu; Fang Wang; Yin-Ke Li (Natural Product Research, 2025)

Toward safe rice production in As-Cd co-contaminated paddy soils: Biogeochemical mechanisms and remediation strategies - Jing-Min Yang; Hui-Lin Chen; Xin Wang; Dong-Xing Guan; Xiong-Hui Ji; Yun-He Xie; Rui Huang; Bo Peng; Qin-Bo Qin (Critical Reviews in Environmental Science and Technology, 2025)

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

Rheology, stability, and physicochemical properties of NaOH-tannic acid solvent for β-chitin dissolution - Shang-Ta Wang; Po-Jou Huang; Szu-Kai Chen; Chia-Rui Shen; Yi-Pin Chen; Min-Lang Tsai (Food Hydrocolloids, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Field and Numerical Investigations on Pumpable Standing Supports Failure Analysis in the Longwall Pre-driven Recovery Room - Dong Zhang; Jianbiao Bai; Zizheng Zhang; Qiancheng Zhu; Min Deng; Shuai Yan; Rui Wang; Shuaigang Liu (Rock Mechanics and Rock Engineering, 2025)

Comparative organic pollutants removal efficiency and life cycle assessment of pyrolysis and solvent elution for industrial waste salt recycling - Xinyu Huang; Hao Wang; Min Song; Rui Chen; Saijun Lv; Haoqing Zhang; Chuqi Wang; Jerome Ramirez; Xiuxiu Ruan (Journal of Environmental Management, 2024)

Visible light-assisted S-doped red mud-based Fe-Co PBA derivatives activated PMS for efficient degradation of oxytetracycline from acidic to alkaline conditions: Degradation mechanism, degradation pathways and toxicity evaluation - Shitong Liu; Jun Wang; Yang Liu; Min Cheng; Baojun Yang; Guangfu Wang; Shichao Yu; Rui Liao; Guanzhou Qiu (Journal of Environmental Chemical Engineering, 2024)

Small object change detection in UAV imagery via a Siamese network enhanced with temporal mutual attention and contextual features: A case study concerning solar water heaters - Shikang Tao; Mengyuan Yang; Min Wang; Rui Yang; Qian Shen (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Concurrent removal of Fe(II), Cu(II), and Zn(II) cations from acid mine drainage by an industrial solid waste - Steel slag: Behaviors and mechanisms - Mingyuan Yang; Cunfang Lu; Shuo Zhang; Yelei Wang; Rui Xu; Min Zhang; Juan Wen; Zilong Li (Environmental Research, 2024)

Vitrification cryo-foil method for shoot tip cryopreservation and virus eradication in apple - Min-Rui Wang; Jun-Hua Bao; Xiao-Yan Ma; Zi-Han Yan; Zhen-Hua Cui; Li-Ying Zhu; Dong Zhang; Qiao-Chun Wang (Cryobiology, 2024)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

The creation of multi-level urban ecological cooling network to alleviate the urban heat island effect - Yingying Li; Shumei Wang; Shujun Zhang; Min Wei; Yongsheng Chen; Xiaoyi Huang; Rui Zhou (Sustainable Cities and Society, 2024)

The relationship between oiliness and mobility and their controlling factors for lacustrine shale oil: A case study of Qing1 Member in Changling Sag, Songliao Basin - Xiao Dianshi; Zheng Lehua; Wang Min; Wang Rui; Guan Xiaodie (Fuel, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Construction of a highly ordered SiC nanofiber@C fiber heterojunction hybrid with a fuzzy grass-like structure for enhanced microwave absorbing performance - Wenzhao Geng; Yilin Liu; Haoyuan Lei; Limeng Song; Hailong Wang; Gang Shao; Yanqiu Zhu; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Reason and control strategy for denitrification and anammox sludge flotation in nitrogen removal process: Mechanisms, strategies and perspectives - Xin Ma; Xin-Rui Zhang; Ying-Jun Sun; Zhi-Han Xi; Jin-Ze Liu; Ze-Tong Feng; Jia-Min Zhou; Xin-Tao Liu; Ying Wang; Ren-Cun Jin; Qian-Qian Zhang (Environmental Research, 2024)

Effect of micro and nanobubble size and concentration on membrane fouling: Strategies for energy-saving and ultrafiltration efficiency enhancement - Nachael Mwanga; Xitong Wang; Pan Li; Yanling Liu; Shengji Xia; Daqiang Yin; Min Rui; Yubin Ye (Desalination, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

Simultaneous removal of nitrate nitrogen and ammonium nitrogen by partial denitrification coupled with anammox synergy by zero-valent iron - Jia-Min Zhou; Ying-Jun Sun; Zhi-Han Xi; Zu-Gang Liao; Xin Ma; Ze-Tong Feng; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Ying Chen; Ren-Cun Jin; Qian-Qian Zhang (Journal of Cleaner Production, 2024)

Impact of long-term conventional and biodegradable film mulching on microplastic abundance, soil structure and organic carbon in a cotton field - Kai Wang; Wei Min; Markus Flury; Anna Gunina; Jun Lv; Qiang Li; Rui Jiang (Environmental Pollution, 2024)

Application of physicochemical techniques to the removal of ammonia nitrogen from water: a systematic review - Tianhong Zhou; Miao Wang; Honglin Zeng; Rui Min; Jinyi Wang; Guozhen Zhang (Environmental Geochemistry and Health, 2024)

Significantly underestimated traffic-related ammonia emissions in Chinese megacities: Evidence from satellite observations during COVID-19 lockdowns - Peilin Chen; Qin'geng Wang; Min Shao; Rui Liu (Chemosphere, 2024)

Understanding secondary particles in a regional site of Yangtze River Delta: Insights from mass spectrometric measurement - Wenfei Zhu; Jialin Shi; Hui Wang; Ying Yu; Rui Tan; Ruizhe Shen; Jun Chen; Shengrong Lou; Min Hu; Song Guo (Science of The Total Environment, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Geological study of an outburst flood event in the upper Yangtze River and risk of similar extreme events - Gang Hu; Guanghui Dong; Tao Liu; Rui Min; Zhijian Yang; Qihui Gao; Huiying Wang; Ping Wang; Jie Chen; Jiafu Zhang; Changsong Wang; Chaoying Zhao; et al. (Global and Planetary Change, 2024)

All chlorination strategy on end-group of guest acceptor enables 18.39 % efficiency and high VOC for ternary organic solar cells - Jixuan Wang; Lei Wang; Rui Sun; Linglong Ye; Bin Zhao; Jie Min; Songting Tan (Chemical Engineering Journal, 2024)

Magnetic media synergistic carbon fiber@Ni/NiO composites for high-efficiency electromagnetic wave absorption - Dalong Tan; Qian Wang; Mengru Li; Limeng Song; Fan Zhang; Zhiyu Min; Hailong Wang; Yanqiu Zhu; Rui Zhang; Di Lan; Bingbing Fan (Chemical Engineering Journal, 2024)

Coupling control of organic and inorganic rock components on porosity and pore structure of lacustrine shale with medium maturity: A case study of the Qingshankou Formation in the southern Songliao Basin - Dianshi Xiao; Lehua Zheng; Jilin Xing; Min Wang; Rui Wang; Xiaodie Guan; Xueyi Guo (Marine and Petroleum Geology, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Discrete element modelling of rotary CPT and its applications - Xiaotong Yang; Ningning Zhang; Jian-Min Zhang; Rui Wang (Computers and Geotechnics, 2024)

An explicit material point and finite volume sequentially coupled method for simulating large deformation problems in saturated soil - Yunyi Li; Jian-Min Zhang; Rui Wang (Computers and Geotechnics, 2024)

Temperature-driven dynamic evolution process of Ag species on silver-loaded Zr0.2Sn0.8O2 catalyst for selective catalytic oxidation of ammonia - Yan Zhang; Zongxiang Yang; Meng Wang; Min Zhang; Caixia Liu; Qingling Liu; Weichao Wang; Ziyin Zhang; Rui Han; Na Ji (Chemical Engineering Journal, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Exogenous application of salicylic acid improves eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple - Xiao-Yan Ma; Jin-Wei Li; Qing Li; Zi-Han Yan; Xi Cheng; Min-Rui Wang; Zhibo Hamborg; Lu Bao; Dong Zhang; Min-Ji Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Artemisia argyi H. Lév. & Vaniot: a comprehensive review on traditional uses, phytochemistry, and pharmacological activities - Wen-Jun Wei; Tao Guo; Gui-Min Xue; Rui Ma; Yuefei Wang; Zhe-Sheng Chen (Phytochemistry Reviews, 2024)

Curcumol: a review of its pharmacology, pharmacokinetics, drug delivery systems, structure–activity relationships, and potential applications - Sicheng Zhai; Rui Wang; Jingyuan Wang; Xiangdong Xu; Le Niu; Min Guo; Yongling Zhang; Yajun Shi; Xuexue Tang (Inflammopharmacology, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Effect of sludge redistribution strategy on stability of partial nitrification-anammox process: Further exploration of the potential value of sludge - Peng Wang; Rui Ou; Jun Tan; Ning Li; Min Zheng; Qinghai Jin; Jin Yu; Di He (Chemosphere, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Early Cretaceous intrusive rocks in the Gangdese arc of southern Tibet do not support shallow subduction of the Neo-Tethyan oceanic lithosphere - Feng Wang; Qing Wang; Di-Cheng Zhu; Shi-Min Li; Peter A. Cawood; Rui-Qiang Wang; Jian-Kang Yi; Liang-Liang Zhang; Jin-Cheng Xie (Lithos, 2024)

Multi-timescale variation characteristics of PM2.5 in different regions of China during 2014–2022 - Rui Liu; Min Shao; Qin'geng Wang (Science of The Total Environment, 2024)

Effective decapsulation method for photovoltaic modules: Limonene-induced EVA controlled swelling under sonication and debonding mechanism analysis - Rui Min; Weikai Deng; Zhi Wang; Tao Qi; Zhihan Zhang; Wanhai Xiao; Guoyu Qian; Dong Wang (Journal of Cleaner Production, 2024)

A novel framework for high resolution air quality index prediction with interpretable artificial intelligence and uncertainties estimation - Junhao Wu; Xi Chen; Rui Li; Anqi Wang; Shutong Huang; Qingli Li; Honggang Qi; Min Liu; Heqin Cheng; Zhaocai Wang (Journal of Environmental Management, 2024)

Mechanisms of benzene and benzo[a]pyrene biodegradation in the individually and mixed contaminated soils - Mukhtiar Ali; Qing Wang; Zhuanxia Zhang; Xing Chen; Min Ma; Zhiwen Tang; Rui Li; Biao Tang; Zhongyuan Li; Xiangfeng Huang; Xin Song (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Predictions of seismic response for sheet-pile wall in liquefiable deposit within LEAP 2022 using the CycLiq constitutive model - Bin Hu-Yan; Rui Wang; Jia-ke Yu; Jian-Min Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

De-branching of starch molecules enhanced the complexation with chitosan and its potential utilization for delivering hydrophobic compounds - Min Liu; Min Zhuang; Dengdeng Li; Jinxu Fan; Rui Wang; Xuanyu Wang; Sheng Ke; Ming Ning; Zhongkai Zhou (Food Hydrocolloids, 2024)

Structural characterization and osteogenic differentiation-promoting activity of polysaccharide purified from Chroogomphus rutilus - Ying Zhou; Lanzhou Li; Zhen Sun; Rui Liu; Yanfeng Zhu; Jingzheng Yi; Yutong Li; Min Hu; Di Wang (Carbohydrate Polymers, 2024)

Study on the mechanism of Panax notoginseng–Salvia miltiorrhiza herb pair on invigorating blood circulation and eliminating blood stasis by blocking the conversion of arachidonic acid to prostaglandin - Rui Zeng; Yuefan Zhang; Shengtong Shi; Xianqin Long; Haixia Zhang; Min Wang; Jianfeng Shi; Ye Jiang; Bin Chen (Journal of Natural Medicines, 2024)

Effects of short and long-term thermal exposure on microbial compositions in soils contaminated with mixed benzene and benzo[a]pyrene: A short communication - Mukhtiar Ali; Xin Song; Qing Wang; Zhuanxia Zhang; Meng Zhang; Min Ma; Jilu Che; Rui Li; Xing Chen; Zhiwen Tang; Biao Tang; Xiangfeng Huang (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

GW4064 inhibits migration and invasion through cathepsin B and MMP2 downregulation in human bladder cancer - Chien-Chang Kao; Chien-Rui Lai; Yi-Hsuan Lin; Tzu-Min Chen; Yu-Ling Tsai; Wen-Chiuan Tsai; Tze-Yun Ong; Hisao-Hsien Wang; Sheng-Tang Wu; Ying Chen (Chemico-Biological Interactions, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Fe(VI) oxidation of synthetic phenolic antioxidants: Kinetics, influencing factors, transformation mechanism and toxicity - Xiaoxue Pan; Fengtao Sun; Min Wang; Hong Sun; Rui Zhang; Mingbao Feng; Xuesheng Zhang (Chemical Engineering Journal, 2024)

Nitrite stimulates HONO and NOx but not N2O emissions in Chinese agricultural soils during nitrification - Yaqi Song; Dianming Wu; Xiaotang Ju; Peter Dörsch; Mengdi Wang; Ruhai Wang; Xiaotong Song; Lingling Deng; Rui Wang; Zhiwei Gao; Haroon Haider; Lijun Hou; et al. (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

Highly sensitive detection of Salmonella based on dual-functional HCR-mediated multivalent aptamer and amplification-free CRISPR/Cas12a system - Zhaohui Qiao; Liangliang Xue; Mengni Sun; Min Zhang; Min Chen; Xia Xu; Wenge Yang; Rui Wang (Analytica Chimica Acta, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Demethylation-Driven ligase chain reaction for simultaneously sensitive detection of m6A demethylase FTO and m1A demethylase ALKBH3 in breast cancer at Single-Molecule level - Ming-hao Liu; Qian Zhang; Wan-tong Yu; Jian-Ge Qiu; Hui-min Yuan; Chuan-rui Wang; Bing-Hua Jiang; Yan Zhang; Chun-yang Zhang (Chemical Engineering Journal, 2023)

Association between urinary phthalate metabolites and chronic obstructive pulmonary disease incidence in US adults: results from NHANES 2007–2018 - Jiran Shen; Yue Wang; Sijing Zhou; Min Tang; Min Li; Rui Han; Guanghe Fei; Ran Wang (Environmental Science and Pollution Research, 2023)

Strategies for enhancing performance of perovskite bismuth ferrite photocatalysts (BiFeO3): A comprehensive review - Tianhong Zhou; Tianjiao Zhai; Huidong Shen; Jinyi Wang; Rui Min; Kai Ma; Guozhen Zhang (Chemosphere, 2023)

Highly photoluminescent tryptophan-coated copper nanoclusters based turn-off fluorescent probe for determination of tetracyclines - Tianru Zou; Shaoqing Li; Guixiang Yao; Rui Qu; Wenrong Yang; Hongbin Wang; Wei Tan; Min Yang (Chemosphere, 2023)

Enhanced nitrogen removal in a pilot-scale AOA-SBFASR system treating municipal wastewater: Process efficiency, microbial community and nitrogen metabolic pathways - Zhi-li Du; Shao-bin Huang; Rui-jian Zhang; Yong-qing Zhang; Hao-tao Dong; Guang-hua Wang; Zhi-min Sun (Journal of Water Process Engineering, 2023)

Intramolecular engineering of defective terminations within triazine-based conjugated polymers for augmented photocatalytic H2 production and Cr(VI) reduction - Zhiquan Jin; Sijia Jin; Shuqi li; Rui Zou; Da Wang; Feilong Dong; Min Liu; Shuang Song; Tao Zeng (Journal of Cleaner Production, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Adsorption of Rhodamine B and Pb(II) from aqueous solution by MoS2 nanosheet modified biochar: Fabrication, performance, and mechanisms - Rui Ma; Daoyuan Nie; Min Sang; Weiwei Wang; Guangze Nie (Bioresource Technology, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Ultrasonic-assisted hypochlorite activation accelerated volatile fatty acids production during sewage sludge fermentation: Critical insights on solubilization/hydrolysis stages and microbial traits - Rui Zhu; Shanshan Zhao; Chenlu Ju; Qing Yang; Chengcheng Cui; Lijuan Wu; Min Wang; Leiyu Feng; Yang Wu (Bioresource Technology, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Decorative ZIF-8 covered facet-dependent Cu2O toward highly efficient adsorption by reduction U(VI) to U(IV) - Xiaomei Zhang; Nina Yan; Min Wang; Xizhi Jiang; Rui Xu; Min Feng; Lei Xu; Shaochun Tang (Journal of Environmental Chemical Engineering, 2023)

Enhanced recovery of germanium(IV) from zinc residue leachate by tartaric acid functionalized chitosan: Experiments and DFT calculation - Hongrui Xiang; Zhihui Yang; Xiaobo Min; Yanjie Liang; Cong Peng; Xiaoyun Liu; Rui Yuan; Qingwei Wang; Feiping Zhao (Hydrometallurgy, 2023)

Effect of a novel joint connection of UHPC wet joint and tapered sleeve locking-type couplers on the lateral cyclic response of precast segmental railway bridge columns - Yuxuan Wang; Zhao Cheng; Shuai Li; Jingquan Wang; Rui Zhong; Min Zeng; Fayan Ming; Bing Cui (Engineering Structures, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Single-stage object detector with local binary pattern for remote sensing images - Kexue Zhou; Min Zhang; Sheng Lin; Rui Zhang; Hai Wang (International Journal of Remote Sensing, 2023)

Gelation mechanism of high soluble dietary fiber okara-egg tofu induced by combined treatment of steam explosion and enzymatic hydrolysis - Nuo Zhao; Jianfu Wu; Xiaoyuan Geng; Chenyang Wang; Tao Wu; Rui Liu; Wenjie Sui; Min Zhang (Food Hydrocolloids, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

PcCLCg is involved in the accumulation of Cl− in shoots for osmotic adjustment and salinity resistance in the Cl−-tolerant xerophyte Pugionium cornutum - Yan-Nong Cui; Zi-Ru Lin; Mei-Mei Cai; Rui-Wen Liu; Suo-Min Wang; Qing Ma (Plant and Soil, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Influence of aboveground structure on connected underground structure seismic response within an integrated system - Wen-Ting Li; Rui Wang; Jian-Min Zhang (Tunnelling and Underground Space Technology, 2023)

A semi-analytical method for predicting train-induced vibrations considering train-track-soil and soil-pile-building dynamic interactions - Zi-Yu Tao; Chao Zou; Guang-Rui Yang; Yi-Min Wang (Soil Dynamics and Earthquake Engineering, 2023)

Comparative studies of transformation behaviors and mechanisms of halophenols in multiple chemical oxidative systems - Xiaoxue Pan; Junyan Wei; Min Wang; Jie Zhang; Zhiming Xu; Haojie Wei; Nami Lai; Kainan Nian; Rui Zhang; Xuesheng Zhang (Science of The Total Environment, 2023)

Thermal and nonthermal effect of microwave irradiation on the pore microstructure and hydrocarbon generation of organic matter in shale - Min Wang; Yuchen Zhang; Jinbu Li; Rui Ma; Xin Wang; Ying Li; Haoming Shao; Jinxu Zhang; Junsheng Fei; Zixiao Deng; Baoxin Pan (Marine and Petroleum Geology, 2023)

Catalytic performances of Cu-ZK-5 zeolites with different template agents in NH3-SCR - Yuchao Zang; Qing Li; Yalian Bi; Caixia Liu; Yan Zhang; Yanhua Wang; Min Zhang; Qingling Liu; Ziyin Zhang; Rui Han (Journal of Environmental Chemical Engineering, 2023)

New insights into photochemical initial concentrations of VOCs and their source implications - Bowei Li; Shaocai Yu; Min Shao; Xinhe Li; Steven Sai Hang Ho; Xiaoyi Hu; Hongli Wang; Rui Feng; Xuekun Fang (Atmospheric Environment, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Long-term performance analysis of BDS-3 precise point positioning (PPP-B2b) service - Shuang Sun; Min Wang; Changjian Liu; Xin Meng; Rui Ji (GPS Solutions, 2023)

Influence of Soil Plug on the Seismic Response of Bucket Foundations in Liquefiable Seabed - Xue-Qian Qu; Rui Wang; Jian-Min Zhang; Ben He (Journal of Marine Science and Engineering, 2023)
The suction installation process for bucket foundations for offshore wind turbines (OWTs) can cause the formation of soil plug within the bucket, which can affect the seismic performance of the OWT. Therefore, it is important to evaluate the influence of soil plug on the seismic performance of OWT on bucket foundations. In this study, a comprehensive set of high-fidelity solid–fluid coupled dynamic numerical simulations are conducted to analyze the seismic response of bucket foundations with a focus on the influence of soil plug and its potential mitigation. The influence of different bucket models, seabed soil densities, seabed inclination and reinforcement types, as well as soil plug removal techniques, are investigated. The results clearly show that the existence of soil plug has a significant unfavorable influence on the seismic performance of OWT on bucket foundations, especially for wide bucket foundations in mildly inclined seabeds, and should be considered in seismic design. Reinforcement methods, such as the application of an inner compartments, outer wings and inner pile, can improve the seismic performance of OWT on bucket foundations, with the application of an inner compartment being the most effective. Soil plug removal can alleviate the negative influence of soil plug, and should be adopted when possible.

Sodium acetate alleviates adverse effects caused by the diet with high proportion of soybean meal in turbot (Scophthalmus maximus L.) - Wentao Wang; Jinjin Zhang; Rui Shao; Shufei Liang; Hui Zhang; Weiqi Xu; Mingzhu Li; Qinghui Ai; Kangsen Mai; Min Wan (Aquaculture, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Biomimetic chitosan nanoparticles with simultaneous water lubricant and anti-inflammatory - Lumin Yang; Haofei Huang; Huajing Zeng; Xiaoduo Zhao; Rui Wang; Zhengfeng Ma; Zengjie Fan; Yong-min Liang; Shuanhong Ma; Feng Zhou (Carbohydrate Polymers, 2023)

P2Y12 receptor gene polymorphisms are associated with epilepsy - Qi Wang; Nan-Rui Shi; Peng Lv; Juan Liu; Ji-Zhou Zhang; Bin-Lu Deng; Yan-Qin Zuo; Jie Yang; Xin Wang; Xiang Chen; Xiu-Min Hu; Ting-Ting Liu; et al. (Purinergic Signalling, 2023)
The basic research indicated that microglial P2Y12 receptors ( P2Y12Rs ) are involved in the pathophysiology of epilepsy through regulated microglial-neuronal interactions, aberrant neurogenesis, or immature neuronal projections. However, whether the clinic case of epilepsy would be associated with P2Y12 receptor gene polymorphisms is presented with few data. In our study, a total of 176 patients with epilepsy and 50 healthy controls were enrolled. Two single-nucleotide polymorphisms, namely rs1491974 and rs6798347, were selected for analysis. The results revealed that carriers of the G allele of rs1491974 G>A or rs6798347 G>A may be associated with an increased risk of epilepsy (OR = 0.576, 95% CI = 0.368–0.901, p = 0.015; OR = 0.603, 95% CI = 0.367–0.988, p = 0.043). Interestingly, we found that the rs1491974 G>A genotype and allele frequencies have only a significant difference in female instead of male case ( p = 0.004 for genotype; p = 0.001 for allele). The subgroup analysis demonstrated that individuals with the rs1491974 G>A genotype might have more frequent seizure (OR = 0.476, 95% CI = 0.255–0.890; p = 0.019). These data implied that both rs1491974 and rs6798347 polymorphisms of P2Y12R would be able to play import roles in epilepsy susceptibility, whereas the rs1491974 polymorphism may be specifically related to seizure frequency.

Changes of Iodine Nutritional Status in the Elderly after Replacing Iodized Salt with Non-Iodized Salt for Half a Year - Min Li; Rui Wang; Jiaxi Lu; Weidong Li; Yichun Hu; Jing Chen; Wei Ma; Lichen Yang (Biological Trace Element Research, 2023)

A stepwise artificial boundary condition for wave propagation in elasto-plastic media - Yunyi Li; Rui Wang; Jian-Min Zhang (Soil Dynamics and Earthquake Engineering, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Butyrate-induced IL-22 expression in fish macrophages contributes to bacterial clearance - Jinjin Zhang; Wentao Wang; Shufei Liang; Rui Shao; Wenkai Shi; Gudmundur H. Gudmundsson; Peter Bergman; Qinghui Ai; Kangsen Mai; Min Wan (Fish & Shellfish Immunology, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Effect of herbaceous plants on the response of loose silty sand slope under rainfall - Pei Tai; Fan Wu; Rui Chen; Jingqi Zhu; Xiong Wang; Min Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

ACC deaminase-encoding Pseudomonas putida arrests seed germination: an alternative strategy for grass and weed control - Di Zhou; Jia-Ling Zhao; Rui Wang; Hai-Lin Wang; Daniela D. Herrera-Balandrano; Tang-Min Chen; Xiao-Feng Lu; Xu-Chu Duan; Mahdi Shahriar; Xin-Chi Shi; Pedro Laborda; Su-Yan Wang (Plant and Soil, 2022)

U-net Models Based on Computed Tomography Perfusion Predict Tissue Outcome in Patients with Different Reperfusion Patterns - Yaode He; Zhongyu Luo; Ying Zhou; Rui Xue; Jiaping Li; Haitao Hu; Shenqiang Yan; Zhicai Chen; Jianan Wang; Min Lou (Translational Stroke Research, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

Pyroptosis participates in PM2.5-induced air–blood barrier dysfunction - Ruxue Jia; Min Wei; Xiao Zhang; Rui Du; Wenping Sun; Lili Wang; Laiyu Song (Environmental Science and Pollution Research, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Genetically encoded redox biosensor system for H2O2 measurement in four subcellular compartments in acute myeloid leukemia (AML) cells - Mengmeng Cui; Ghulam Abbas; Dianbing Wang; Qian Liu; Rui Gong; Min Li; Xian-En Zhang (Science China Life Sciences, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)

ROS-induced oxidative stress in plant cryopreservation: occurrence and alleviation - Li Ren; Min-Rui Wang; Qiao-Chun Wang (Planta, 2021)
Main conclusion Reactive oxygen species (ROS)-induced oxidative stress results in low success or even total failure of cryopreservation. Better understanding of how the plant establishes resistance/tolerance to ROS-induced oxidative stress facilitates developments of robust cryopreservation procedures. Abstract Cryopreservation provides a safe and efficient strategy for long-term preservation of plant genetic resources. ROS-induced oxidative stress caused damage to cells and reduced the ability of the plant to survive following cryopreservation, eventually resulting in low success or even total failure. This paper provides updated and comprehensive information obtained in the past decade, including the following: (1) ROS generations and adaptive responses of antioxidant systems during cryopreservation; (2) expressions of oxidative stress-associated genes and proteins during cryopreservation; (3) ROS-triggered programmed cell death (PCD) during cryopreservation; and (4) exogenous applications of enzymatic and non-enzymatic antioxidants in improving success of cryopreservation. Prospects for further studies are proposed. The goal of the present study was to facilitate better understanding of the mechanisms by which the plant establishes resistance/tolerance to oxidative stress during cryopreservation and promote further studies toward the developments of robust cryopreservation procedures and wider application of plant cryobiotechnology.

Detoxification difference of cadmium between the application of selenate and selenite in native cadmium-contaminated soil - Mingxing Qi; Yang Liu; Yanan Li; Min Wang; Nana Liu; Pornpimol Kleawsampanjai; Fei Zhou; Hui Zhai; Mengke Wang; Quang Toan Dinh; Rui Ren; Dongli Liang (Environmental Science and Pollution Research, 2021)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Solid-Fluid Coupled Numerical Analysis of Suction Caisson Installation in Sand - He Wang; Rui Wang; Jian-Min Zhang (Journal of Marine Science and Engineering, 2021)
Suction caissons are widely used foundations in offshore engineering. The change in excess pore pressure and seepage field caused by penetration and suction significantly affects the soil resistance around the caisson wall and tip, and also affects the deformation of the soil within and adjacent to the caisson. This study uses Arbitrary Lagrangian–Eulerian (ALE) large deformation solid-fluid coupled FEM to investigate the changes in suction pressure and the seepage field during the process of the suction caisson installation in sand. A nonlinear Drucker-Prager model is used to model soil, while Coulomb friction is applied at the soil-caisson interface. The ALE solid-fluid coupled FEM is shown to be able to successfully simulate both jacked penetration and suction penetration caisson installation processes in sand observed in centrifuge tests. The difference in penetration resistance for jacked and suction installation is found to be caused by the seepage and excess pore pressure generated during the suction caisson installation, highlighting the importance of using solid-fluid coupled effective stress-based analysis to consider seepage in the evaluation of suction caisson penetration.

Assessments of rooting, vegetative growth, bulb production, genetic integrity and biochemical compounds in cryopreserved plants of shallot - Min-Rui Wang; Zhibo Hamborg; Rune Slimestad; Abdelhameed Elameen; Dag-Ragnar Blystad; Sissel Haugslien; Gry Skjeseth; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Advances in cryopreservation of in vitro-derived propagules: technologies and explant sources - Min-Rui Wang; Maurizio Lambardi; Florent Engelmann; Ranjith Pathirana; Bart Panis; Gayle M. Volk; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

Metabolomics Study of Flavonoids and Anthocyanin-Related Gene Analysis in Kiwifruit (Actinidia chinensis) and Kiwiberry (Actinidia arguta) - Min Yu; Yuping Man; Rui Lei; Xuemei Lu; Yanchang Wang (Plant Molecular Biology Reporter, 2020)
This study investigated the flavonoid compounds in Actinidia chinensis and Actinidia arguta fruits. A total of 125 flavonoids, including 9 anthocyanins, 12 catechins, 17 flavanones, 48 flavones (including 14 flavone C-glycosides), 29 flavonols, 6 isoflavones, and 4 proanthocyanidins, were identified in “Hongyang” kiwifruit (red flesh), “Jintao” kiwifruit, “Mini Amethyst” kiwiberry (purple flesh), and “Kuilv” kiwiberry. Thirty-nine metabolites showed significantly different contents between “Hongyang” and “Jintao,” and 38 of them showed higher content in “Hongyang,” whereas 39 metabolites showed significantly different contents between “Mini Amethyst” and “Kuilv,” and 31 of them showed higher content in “Mini Amethyst.” This result indicates the superior nutritional value of the pigmented kiwi cultivars in terms of flavonoids. Multivariate statistical analysis indicates that the variation in flavonoid profiles contributes to the pigmentation phenotypes of “Hongyang” and “Mini Amethyst.” Further comparative transcriptomic analysis revealed that structural genes in the anthocyanin synthesis pathway ( AcF3H , AcF3′H , AcDFR , AcUFGT ) and transcription factors ( AcMYB10 , AcbHLH5 ) may be involved in the pigmentation of the red-fleshed A. chinensis , whereas AaF3H , AaF3GT , and AaMYB110 may play important roles in the pigmentation of the purple-fleshed A. arguta . This study provides broader insight into the variation in flavonoid profiles among kiwifruit/berry, evaluates the flavonoid nutrition of the four cultivars, and provides additional evidence for the correlation between the genes and metabolites involved in flavonoid synthesis.

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Thallus sectioning as an efficient monospore release method in Pyropia yezoensis (Bangiales, Rhodophyta) - Nianci Chen; Lei Tang; Xiaowei Guan; Rui Chen; Min Cao; Yunxiang Mao; Dongmei Wang (Journal of Applied Phycology, 2020)
The red seaweed Pyropia yezoensis is a marine crop of important economic value and is widely cultivated in the coastal areas of northern China. The current seedling-raising system relies on the germination of conchospores, a process not fast enough to meet the increasing demand from farmers. In this study, we developed a monospore-dependent seedling method based on the asexual reproduction of the Pyropia thallus. The Pyropia thallus was physically sectioned into small pieces (microthalli) that were cultivated at 15 °C. The algal cells in the microthalli became morphologically condensed, underwent cell division, and then developed into monospores on the 5th day. The monospores were able to attach to the seeding rope in 24 h and germinated into healthy thalli. To optimize the efficiency of monospore release, we tested the effect of temperature and the size and original positions of the microthalli as well as the age of the mother thallus. Microthalli with a size of 30–50 cells from the middle and apex of 21-day-old thalli cultivated at 15 ° C yielded the optimum production of monospores. Theoretically, in this thallus-to-thallus seeding strategy, 0.1 g of thallus could produce at least 10 7 monospores, with the same number of offspring thallus seedlings. Taking all of these advantages together, including the high efficiency, short time, low cost and easy operation, this physical sectioning method could serve as a promising seed source especially for new cultivars with superior traits in Pyropia farming and rapid replenishment of seedlings when thalli undergo disastrous diseases.

Transcriptome Profile Analysis of Resistance Inoculated by Dryopteris crassirhizoma Dryocrassin ABBA in Potato Tubers - Wenzhong Wang; Rui Gao; Tong Zhang; Lingling Chen; Peng Feng; Zongbao Zhao; Changxu Zhang; Fanxiang Min; Shuai Yang; Qi Wei; Mei Guo; Ying Chang (American Journal of Potato Research, 2020)

Responses of Alpine Wetlands to Climate Changes on the Qinghai-Tibetan Plateau Based on Remote Sensing - Rui Wang; Min He; Zhenguo Niu (Chinese Geographical Science, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Droplet-vitrification for shoot tip cryopreservation of shallot (Allium cepa var. aggregatum): effects of PVS3 and PVS2 on shoot regrowth - Min-Rui Wang; Zhibo Zhang; Jiří Zámečník; Alois Bilavčík; Dag-Ragnar Blystad; Sissel Haugslien; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)

Effects of Exogenous Application of Melatonin on Quality and Sugar Metabolism in ‘Zaosu’ Pear Fruit - Jianlong Liu; Rongrong Yue; Min Si; Meng Wu; Liu Cong; Rui Zhai; Chengquan Yang; Zhigang Wang; Fengwang Ma; Lingfei Xu (Journal of Plant Growth Regulation, 2019)

Roseosporol A, the first isolation of a novel sesquiterpenoid from Streptomyces roseosporus - Lina Deng; Rui Wang; Guowei Wang; Mingxu Liu; Zhihua Liao; Guojian Liao; Min Chen (Natural Product Research, 2019)

The severity of drought and precipitation prediction in the eastern fringe of the Tibetan Plateau - Yang Zhao; Xiangde Xu; Liufeng Liao; Yuhong Wang; Xiaoping Gu; Rui Qin; Yunyun Guo; Zhaoping Kang; Fang Wang; Min Wang (Theoretical and Applied Climatology, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

In vitro tissue culture of apple and other Malus species: recent advances and applications - Jaime A. Teixeira da Silva; Andrea Gulyás; Katalin Magyar-Tábori; Min-Rui Wang; Qiao-Chun Wang; Judit Dobránszki (Planta, 2019)

Identification of genes revealed differential expression profiles and lignin accumulation during leaf and stem development in tea plant (Camellia sinensis (L.) O. Kuntze) - Yong-Xin Wang; Rui-Min Teng; Wen-Li Wang; Ying Wang; Wei Shen; Jing Zhuang (Protoplasma, 2019)

Identification of the complete mitochondrial genome of Garra pingi pingi (Cypriniformes, Cyprinidae) - Yuan-Chao Zou; Mei Chen; Chuan-Jie Qin; Yong-Ming Wang; Rui Li; Ze-Min Qi; Zheng-Yong Wen (Conservation Genetics Resources, 2018)

A new isoflavanone from Ficus tikoua Bur - Si-Yu Zhou; Rui Wang; Li-Qing Deng; Xiao-Long Zhang; Min Chen (Natural Product Research, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

AFLP analysis revealed a north to south genetic break in the brown alga Sargassum thunbergii along the coast of China - Juan Liu; Dongmei Zhan; Rui Zhang; Lu Zeng; Gaoge Wang; Zi-Min Hu (Journal of Applied Phycology, 2018)

Cryobiotechnology of apple (Malus spp.): development, progress and future prospects - Min-Rui Wang; Long Chen; Jaime A. Teixeira da Silva; Gayle M. Volk; Qiao-Chun Wang (Plant Cell Reports, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

U–Pb zircon, geochemical and Sr–Nd–Hf isotopic constraints on age and origin of the intrusions from Wunugetushan porphyry deposit, Northeast China: implication for Triassic–Jurassic Cu–Mo mineralization in Mongolia–Erguna metallogenic belt - Kui-Feng Mi; Zhen-Jiang Liu; Rui-Bin Liu; Chun-Feng Li; Jian-Ping Wang; Run-Min Peng (International Geology Review, 2018)

Cryobiotechnology of forest trees: recent advances and future prospects - Jing-Wei Li; Elif Aylin Ozudogru; Jiao Li; Min-Rui Wang; Wen-Lu Bi; Maurizio Lambardi; Qiao-Chun Wang (Biodiversity and Conservation, 2018)

Enhanced phosphorus removal using acid-treated magnesium slag particles - Xianqiang Tang; Rui Li; Min Wu; Lei Dong; Zhenhua Wang (Environmental Science and Pollution Research, 2018)

A new cinnamic acid glycoside from roots of Heracleum dissectum - Zhi-Gang Wang; Jie Mi; Xin-Rui Wang; Ya-Yu Huo; Ya-Jie Peng; Hai-Min Zhang; Yang Gao; Hai-Long Zhang (Natural Product Research, 2018)

Prospect of recovering phosphorus in magnesium slag-packed wetland filter - Xianqiang Tang; Min Wu; Rui Li; Zhenhua Wang (Environmental Science and Pollution Research, 2017)

Correlation of rs9331888 polymorphism with Alzheimer’s disease among Caucasian and Chinese populations: a meta-analysis and systematic review - Bin Zhu; Rui Min Wang; Jian Ting Wang; Rui Ling Chen; Yan Fei Zheng; Lei Zhang; Zhi Gang Zhao (Metabolic Brain Disease, 2017)

Site-directed mutagenesis under the direction of in silico protein docking modeling reveals the active site residues of 3-ketosteroid-Δ1-dehydrogenase from Mycobacterium neoaurum - Ning Qin; Yanbing Shen; Xu Yang; Liqiu Su; Rui Tang; Wei Li; Min Wang (World Journal of Microbiology and Biotechnology, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

The ROS derived mitochondrial respirstion not from NADPH oxidase plays key role in Celastrol against angiotensin II-mediated HepG2 cell proliferation - Xin Liu; Rui-wei Gao; Miao Li; Chun-feng Si; Yong-peng He; Min Wang; Ying Yang; Qing-yin Zheng; Chao-yun Wang (Apoptosis, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Functional analysis of a chitinase gene during the larval-nymph transition in Panonychus citri by RNA interference - Wen-Kai Xia; Xiao-Min Shen; Tian-Bo Ding; Jin-Zhi Niu; Rui Zhong; Chong-Yu Liao; Ying-Cai Feng; Wei Dou; Jin-Jun Wang (Experimental and Applied Acarology, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Xenoliths in ultrapotassic volcanic rocks in the Lhasa block: direct evidence for crust–mantle mixing and metamorphism in the deep crust - Rui Wang; William J. Collins; Roberto F. Weinberg; Jin-xiang Li; Qiu-yun Li; Wen-yan He; Jeremy P. Richards; Zengqian Hou; Li-min Zhou; Richard A. Stern (Contributions to Mineralogy and Petrology, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

Culture of shoot tips from adventitious shoots can eradicate Apple stem pitting virus but fails in Apple stem grooving virus - Min-Rui Wang; Bai-Quan Li; Chao-Hong Feng; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Sequence Characteristics and Phylogenetic Implications of the nrDNA Internal Transcribed Spacers (ITS) in Protospecies and Landraces of Sugarcane (Saccharum officinarum L.) - Cui-Feng Yang; Li-Tao Yang; Yang-Rui Li; Ge-Min Zhang; Chun-Ya Zhang; Wei-Zan Wang (Sugar Tech, 2016)

Impact of climate change on regional irrigation water demand in Baojixia irrigation district of China - Xiao-jun Wang; Jian-yun Zhang; Mahtab Ali; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Zhuo Jiang (Mitigation and Adaptation Strategies for Global Change, 2016)

Adaptation to climate change impacts on water demand - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; En-hong Guan; Yong-xiang Wu; Juan Gao; Rui-min He (Mitigation and Adaptation Strategies for Global Change, 2016)

Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Effect of irrigation on the soil respiration of constructed grasslands in Inner Mongolia, China - Ji–Rui Gong; Sha Xu; Yihui Wang; Qinpu Luo; Min Liu; Wei Zhang (Plant and Soil, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Marinactinospora endophytica sp. nov., isolated from a medicinal plant - Min-Jiao Liu; Thi-Nhan Khieu; Rui Gao; Wael N. Hozzein; Hong-Fei Wang; Wei Yang; Salam Nimaichand; Zhi Xiong; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

PtAKT1 maintains selective absorption capacity for K+ over Na+ in halophyte Puccinellia tenuiflora under salt stress - Pei Wang; Qiang Guo; Qian Wang; Xiang-Rui Zhou; Suo-Min Wang (Acta Physiologiae Plantarum, 2015)

Historic water consumptions and future management strategies for Haihe River basin of Northern China - Xiao-jun Wang; Jian-yun Zhang; Zhi-feng Yang; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Hong-wei Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Potential impact of climate change on future water demand in Yulin city, Northwest China - Wang Xiao-jun; Zhang Jian-yun; Shahid Shamsuddin; He Rui-min; Xia Xing-hui; Mou Xin-li (Mitigation and Adaptation Strategies for Global Change, 2015)

Association of microRNA-3144 variant with the susceptibility to hepatocellular carcinoma - Jun Zhang; Rui Wang; Min Cai; Shunji Yu; Yanyun Ma; Weihong Xu; Chunfang Gao; Jiucun Wang; Lifang Hou; Yi Liu; Jie Liu (Genes & Genomics, 2014)

Research on hydrochemical spatio-temporal characteristics of groundwater quality of different aquifer systems in Songhua River Basin, eastern Songnen Plain, Northeast China - Rui Wang; Jian-Min Bian; Yue Gao (Arabian Journal of Geosciences, 2014)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Mechanism and comprehensive countermeasure for drought management from the view of catastrophe theory - Xiao-jun Wang; Jian-yun Zhang; Xue-wei Tong; Shahid Shamsuddin; Rui-min He; Xing-hui Xia (Natural Hazards, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

An Endophytic Sanguinarine-Producing Fungus from Macleaya cordata, Fusarium proliferatum BLH51 - Xue-Jun Wang; Chang-Li Min; Mei Ge; Rui-Hua Zuo (Current Microbiology, 2014)

MicroRNA-128 regulates the differentiation of rat bone mesenchymal stem cells into neuron-like cells by Wnt signaling - Rui Wu; Yue Tang; Wenqiao Zang; Yuanyuan Wang; Min Li; Yuwen Du; Guoqiang Zhao; Yuming Xu (Molecular and Cellular Biochemistry, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

Comprehensive identification of high-frequency and co-occurring Mafa-DPA1, Mafa-DQA1, Mafa-DRA, and Mafa-DOA alleles in Vietnamese cynomolgus macaques - Ruirui Xiang; Huiling Zhang; Qing Deng; Rui Yue; Haite Tang; Yanqi Zhang; Fei Ling; Min Zhuo; Hongli Du; Shiqian Xu; Qiang Xu; Xiaoning Wang (Immunogenetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

DNA polymerase beta promoter mutations affect gene transcription, translation and the sensitivity of esophageal cancer cells to cisplatin treatment - Tao Wang; Wenqiao Zang; Yunyun Ma; Min Li; Xiaoyan Xuan; Na Wang; Rui Wu; Yuebai Li; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Overexpression of a Transcription Factor OsMADS15 Modifies Plant Architecture and Flowering Time in Rice (Oryza sativa L.) - Sun-Jie Lu; He Wei; Ya Wang; Hui-Mei Wang; Rui-Fang Yang; Xiao-Bo Zhang; Ju-Min Tu (Plant Molecular Biology Reporter, 2012)

Water resources management strategy for adaptation to droughts in China - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Amgad ElMahdi; He Rui-min; Bao Zhen-xin; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

Distribution and linkage disequilibrium analysis of polymorphisms of MC4R, LEP, H-FABP genes in the different populations of pigs, associated with economic traits in DIV2 line - Zhe Chao; Feng Wang; Chang-Yan Deng; Li-Min Wei; Rui-Ping Sun; Hai-Long Liu; Quan-Wei Liu; Xin-Li Zheng (Molecular Biology Reports, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

Expression and Clinical Significance of CK19 and CK20 Expressions in Transverse Mesocolon Biopsies from Patients with Gastric Carcinoma - Guo-Rui Sun; Xiao-Yuan Dong; Qing-Si He; Hui Qu; Yan-Min Wang (Cell Biochemistry and Biophysics, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Gini coefficient to assess equity in domestic water supply in the Yellow River - Xiao-jun Wang; Jian-yun Zhang; Shamsuddin Shahid; Amgad ElMahdi; Rui-min He; Xin-gong Wang; Mahtab Ali (Mitigation and Adaptation Strategies for Global Change, 2012)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

A strategy to deal with water crisis under climate change for mainstream in the middle reaches of Yellow River - Xiao-jun Wang; Jian-yun Zhang; Rui-min He; ElMahdi Amgad; ElSawah Sondoss; Man-ting Shang (Mitigation and Adaptation Strategies for Global Change, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly - Xiao-Li Li; Gui-Rong Wang; Yuan-Yuan Jing; Ming-Ming Pan; Chen-Fang Dong; Rui-Min Zhou; Zhao-Yun Wang; Qi Shi; Chen Gao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Mechanisms underlying low [Ca2+]o-induced increased excitability of hippocampal neurons - Wei-Dong Yue; Yun-Hong Zhang; Feng Gu; Jing Wang; Ji-Ye Zhang; Rui-Min Gu (Neuroscience Bulletin, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Changes of Bt Toxin in the Rhizosphere of Transgenic Bt Cotton and its Influence on Soil Functional Bacteria - Yu-Kui Rui; Guo-Xiang Yi; Jing Zhao; Bao-Min Wang; Zhao-Hu Li; Zhi-Xi Zhai; Zhong-Pei He; Qing X. Li (World Journal of Microbiology and Biotechnology, 2005)

Identification of a novel rice bZIP-type transcription factor gene,OsbZIP1, involved in response to infection ofMagnaporthe grisea - Xiang-Bing Meng; Wen-Sheng Zhao; Rui-Ming Lin; Min Wang; You-Liang Peng (Plant Molecular Biology Reporter, 2005)

Molecular cloning and characterization of four isoforms of mCKLF, mouse homologues of human chemokine-like factor - Min Rui; Donglan Xia; Yingmei Zhang; Wenling Han; Lu Wang; Peiguo Ding; Yingcheng Zhong; Quansheng Song; Dalong Ma (Molecular Biology Reports, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)